From Contact to Enact: Reducing Prejudice Toward Physical Disability Using Engagement Strategies - Martiny, Kristian Moltke; Scott-Fordsmand, Helene; Jensen, Andreas Rathmann; Juhl, Asger; Nielsen, David Eskelund; Corneliussen, Thomas (Frontiers in Psychology, 2022)
The contact hypothesis has dominated work on prejudice reduction and is often described as one of the most successful theories within social psychology. The hypothesis has nevertheless been criticized for not being applicable in real life situations due to unobtainable conditions for direct contact. Several indirect contact suggestions have been developed to solve this ‘application challenge’. Here we suggest a hybrid strategy of both direct and indirect contact. Based on the second-person method developed in social psychology and cognition, we suggest working with an engagement strategy as a hybrid hypothesis. We expand on this suggestion through an engagement-based intervention, where we implement the strategy in a theater performance and investigate the effects on prejudicial attitudes toward people with physical disabilities. Based on the results we reformulate our initial engagement strategy into the Enact (Engagement, Nuancing, and Attitude formation) hypothesis. To deal with the application challenge, this hybrid hypothesis posits two necessary conditions for prejudice reduction. Interventions should: 1) work with engagement to reduce prejudice, and 2) focus on the second-order level of attitudes formation. Here the aim of the prejudice reduction is not attitude correction, but instead the nuancing of attitudes.